PENGENALAN BUDIDAYA MAGGOT SEBAGAI SOLUSI PENGELOLAAN SAMPAH DAN PENDUKUNG PARIWISATA BERKELANJUTAN DI DESA CIAKAR, KABUPATEN TANGERANG - Julita Then; Johannes Kurniawan; Reagan Brian (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2025)
Ciakar Village in Panongan District, Tangerang Regency, has great potential as an eco-based agro-tourism area due to its agricultural resources and active community groups such as farmer groups (POKTAN) and women’s associations (PKK). However, the village faces major challenges, including suboptimal management of household organic waste and agricultural residues, as well as the previous failure of Black Soldier Fly (BSF) maggot cultivation. This Community Service Program aims to provide an appropriate technological solution through training on BSF maggot cultivation as an efficient and economically valuable method of organic waste management. The implementation method consists of three stages: (1) interviews and field observations to map existing conditions; (2) technical training on maggot cultivation, organic waste processing, construction of semi-permanent cages using local materials, and socialization of waste separation; and (3) evaluation through reflection and the formation of a sustainable management team. The results show increased knowledge and skills among partners in maggot cultivation and waste management, as well as higher awareness of environmental issues. A prototype BSF maggot cage made from bamboo was produced, and a joint management group from POKTAN and PKK was established. This program creates new economic opportunities and supports the development of Ciakar Village as an educational agro-tourism destination.